BSA-PEG Hydrogel: A Novel Protein-Ligand Binding 3D Matrix - Coelho, Carlos D. F. (2022)
Hydrogel materials have good biomimetic properties and high potential for biomedical and bioanalytical applications. In this work, a hydrogel of serum albumin crosslinked with poly-(ethylene glycol) was prepared and characterized for its water content, protein structure and stability. The ability of the hydrogel to bind small molecule ligands with different hydrophobicity was evaluated using a homologous series of amphiphiles (NBD-Cn, n = 4, 6 and 8) and the calculated binding affinities were similar to that of free protein in solution. Overall, the results indicate this type of hydrogel system as a convenient tool for studying the binding of xenobiotics to tissue proteins.